How much mediation in dynamic assessment for gifted students? Up to critical thinking please!. (January 2017) - Sahragard, Rahman; Heidari, Kamal
Reviewing the assessment literature, dynamic assessment is the most recently advocated type of assessment in that it not only argues for integration between assessment and instruction, but also takes into consideration the testees' past, present, and future potentials. However, as far as dynamic assessment is concerned, a key question is: How much assistance, or mediation, should be provided by the assessor? Most studies are at the level of theory, and putting the theory into practice is not that easy. The same question is more salient for gifted students. Should they be provided with the same degree of mediation as is provided for other students? The current paper makes an attempt to provide a more practical and understandable answer to this question. To achieve the goal, the authors refer to the concept of critical thinking and, after clarifying it, responds to the above-mentioned question by maintaining that helping gifted students reach the threshold level of critical thinking should be the final point of assisting learners in an assessment session.